Overview Petrochemical Based Industries in Malaysia - Mohamad Rojl Sarmldi; Ramlan Aziz; Mohammed Azlan Hussain; Wan Ramli Wan Daud (Department of Chemical Engineering, Universitas Gadjah Mada, 2001)
This paper describes the current status of the petrochemical industry in Malaysia. The industry is broadly categorized into various sector that include the agrochemical and agroprocessing, basic chemicals, industrial gases, oleochemical, petrochemical, surface coatings, and the fine chemicalssector. With regard to industrial development, Malaysia has adopted the Manufacturing strategy and clustering concept for the manufacturing based industry. The main idea is to develop the chemical industry in the form of an industrial clusterwhere industrial symbiosis could tloulish and achieve the national objectives within the next ten years or so. The focus of the paper is, however, on the resource based processing and petrochemical industry in particular.